Advances in barrier coatings and film technologies for achieving sustainable packaging of food products – A review. (September 2021) - Tyagi, Preeti; Salem, Khandoker Samaher; Hubbe, Martin A.; Pal, Lokendra
Abstract: Background: The technology of food packaging is responding to significant market dynamics such as the rapid growth in e-commerce and preservation of fresh food, a sector that accounts for over 40% of plastic waste. Further, mandates for sustainability and recent changes in national governmental policies and regulations that include banning single-use plastic products as observed in sweeping reforms in Europe, Asia, and several US States are forcing industries and consumers to find alternative solutions. Scope and approach: This review highlights an ongoing shift of barrier coatings from traditional synthetic polymers to sustainable breakthrough materials for paper-based packaging and films. Advantages, challenges and adapting feasibility of these materials are described, highlighting the implications of selecting different materials and processing options. A brief description on progress in methods of coating technologies is also included. Finally, the end fate of the barrier materials is classified depending on the packaging type, coating materials used and sorting facility availability. Key findings and conclusions: Different types of coatings, such as water-based biopolymers, due to their greater environmental compatibility, are making inroads into more traditional petroleum-based wax and plastic laminate paperboard products for fresh food bakery, frozen food, and take-out containers applications. In addition, nano-biocomposites have been studied at an accelerating pace for developing active and smart packaging. Based on the momentum of recent developments, a strong pace of continuing developments in the field can be expected. Graphical abstract: Image 1 Highlights: Top trends in food packaging are driven by sustainability, e-commerce, and the end fate of the materials. Recent developments in bio-based materials have the potential of replacing petro-based polymers. High speed and specialized coating methods have emerged in the past few years for food packaging development. Businesses are focused on the recycling of synthetic and biopolymers.